Multisensor observations of the Amazon-Orinoco river plume interactions with hurricanes - Reul, Nicolas; Quilfen, Yves; Chapron, Bertrand; Fournier, Severine; Kudryavtsev, Vladimir; Sabia, Roberto (Journal of Geophysical Research: Oceans, 2014)
An analysis is presented for the spatial and intensity distributions of North Atlantic extreme atmospheric events crossing the buoyant Amazon-Orinoco freshwater plume. The sea surface cooling amplitude in the wake of an ensemble of storm tracks traveling in that region is estimated from satellite products for the period 1998-2012. For the most intense storms, cooling is systematically reduced by approximate to 50% over the plume area compared to surroundings open-ocean waters. Historical salinity and temperature observations from in situ profiles indicate that salt-driven vertical stratification, enhanced oceanic heat content, and barrier-layer presence within the plume waters are likely key oceanic factors to explain these results. Satellite SMOS surface salinity data combined with in situ observations are further used to detail the oceanic response to category 4 hurricane Igor in 2010. Argo and satellite measurements confirm the haline stratification impact on the cooling inhibition as the hurricane crossed the river plume. Over this region, the SSS mapping capability is further tested and demonstrated to monitor the horizontal distribution of the vertical stratification parameter. SMOS SSS data can thus be used to consistently anticipate the cooling inhibition in the wake of TCs traveling over the Amazon-Orinoco plume region.